POSTGRADUATE RESEARCH IN ISLAMIC THOUGHT AND CIVILIZATION AT THE INTERNATIONAL INSTITUTE OF ISLAMIC THOUGHT AND CIVILIZATION (ISTAC), MALAYSIA - Abdul Rahman, Mohd Zain (Malaysian Journal of Library and Information Science, 2005)
The purpose of this study is to examine the research trends based on the master’s and doctoral dissertations submitted to the International Institute of Islamic Thought and Civilization (ISTAC) from 1991 to 2004. Besides consulting the listing of the theses produced by the library, physical inspection for each theses and dissertation available in ISTAC library had been carried out in order to ascertain the accuracy of information. In addition, a compilation of thesis abstracts from 1993-2000 which was published in al-Shajarah, the journal of the institute, was also used as the source of reference for this study. Since its establishment in 1991 till 2004, ISTAC had successfully produced 20 doctoral dissertations and 58 master’s theses through the supervision of 23 distinguished supervisors at the institute.